Exogenous Nitric Oxide Enhances Disease Resistance by Nitrosylation and Inhibition of S-Nitrosoglutathione Reductase in Peach Fruit - Yu, Zifei; Cao, Jixuan; Zhu, Shuhua; Zhang, Lili; Peng, Yong; Shi, Jingying (Frontiers in Plant Science, 2020)
Nitric oxide (NO), a signaling molecule, participates in defense responses during plant-pathogen interactions. S-nitrosoglutathione (GSNO) is found to be an active intracellular NO storage center and regulated by S-nitrosoglutathione reductase (GSNOR) in plants. However, the role of GSNOR in NO induced disease resistance is not clear. In this research, the effects of NO and GSNOR inhibitor (N6022) on the defense response of harvested peach fruit to Monilinia. fructicola infection were investigated. It was found that the disease incidence and lesion diameter of peach fruits were markedly (P < 0.05) reduced by NO and GSNOR inhibitor. However, the expression of GSNOR was significantly enhanced (P < 0.05) by NO only during 2~6 h. Analyses using iodo-TMT tags to detect the nitrosylation sites of GSNOR, revealed that the sulfhydryl group of the 85-cysteine site was nitrosylated after NO treatment in peach fruit at 6 and 12 h, suggesting that exogenous NO enhances disease resistance via initial inhibition of gene expression and the S-nitrosylation of GSNOR, thereby inhibiting GSNOR activity. Moreover, NO and GSNOR inhibitor enhanced the expression of systemic acquired resistance (SAR) related genes, such as, pathogenesis-related gene 1 (PR1), non expressor of PR1 (NPR1), and TGACG-binding factor 1 (TGA1). These results demonstrated that S-nitrosylation of GSNOR protein and inhibition of GSNOR activity contributed to the enhanced disease resistance in fruit.